2023
DOI: 10.1002/anie.202302436
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Defect Generation Strategy for Efficient Enzyme Immobilization in Robust Metal‐Organic Frameworks for Catalytic Hydrolysis and Chiral Resolution

Abstract: Enzyme immobilization has been demonstrated to be a favorable protocol for promoting the industrialization of bioactive molecules, but still with formidable challenge. Addressing this challenge, we create a dynamic defect generation strategy for enzyme immobilization by using the dissociation equilibrium of metal‐organic frameworks (MOFs) mediated by enzymes. Enzymes can act as “macro ligands” to generate competitive coordination against original ligands, along with the release of metal clusters of MOFs to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Several enzymes, including lipase, catalase, and glucose oxidase, have been successfully immobilized in UiO-66, showing good enzymatic activities and stability. Furthermore, this approach offers broad applicability, presenting a cost-effective alternative to the ball milling method for industrial MOF-based composite production …”
Section: Applications Of Enzyme–mof Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several enzymes, including lipase, catalase, and glucose oxidase, have been successfully immobilized in UiO-66, showing good enzymatic activities and stability. Furthermore, this approach offers broad applicability, presenting a cost-effective alternative to the ball milling method for industrial MOF-based composite production …”
Section: Applications Of Enzyme–mof Compositesmentioning
confidence: 99%
“…Furthermore, this approach offers broad applicability, present-ing a cost-effective alternative to the ball milling method for industrial MOF-based composite production. 67 Recently, a particular focus on the fabrication of MOF− enzyme-composite-based devices has emerged. 105 Bell et al reported a facile method of interfacial crystallization to integrate enzyme-encapsulated MOF crystals onto the reactive shell-side of hollow fiber membranes.…”
Section: Applications Of Enzyme−mof Compositesmentioning
confidence: 99%
“…Our other work used proteins as “hoes” to infiltrate enzymes into the structure by “picking” the structure of the MOF. Enzymes serve as macro ligands to generate competitive coordination against original ligands, along with the release of metal clusters of MOFs to generate defects, facilitating the transport of enzymes from the surface to the structure’s interior . In the sacrificial templating strategy, we selected MOFs such as ZIF-90 and ZPF-2 that can efficiently load and protect various biologically active macromolecules while remaining digestible under mild acidic conditions as cores.…”
Section: Enzyme-immobilization Strategiesmentioning
confidence: 99%
“…Super-resolution microscopy (SRM) represents one of the most used standard methods for three-dimensional biological imaging, especially with the development of new types of fluorophores (such as Alexa Fluor, ATTO, and Cy dyes) that have high quantum yields, high photostability, and more importantly, minimal effects on labeled biomolecules. Chen and co-workers used structured illumination microscopy (SIM) to reveal the dynamic defect generation strategy of enzymes infiltrating onto UiO-66 . Yet, SIM can only obtain a spatial resolution of ∼120 nm by mathematical deconvolution of interference patterns .…”
Section: Introductionmentioning
confidence: 99%